Relationship between social capital and technology transfer performance: A study on companies in technology park - Abidin, Rahimi; Hasnan, Norlena; Abdullah, Che Sobry; Mohtar, Shahimi; Zulhumadi, Faisal (IBIMA Publishing, 2013)
Tacit knowledge and personal experience of an individual can only be obtained in a tacit manner.Social capital is a prominent concept that provides a foundation to describe and characterize the properties.Therefore social interaction is very important to facilitate technological knowledge transfer among the units within an organisation.This paper aims to contribute to the existing knowledge in the field of technology transfer by exploring the concept of social capital.It discusses the technology transfer performance and focuses on the important firm-specific asset, which is social capital.By using the data from a survey on industrial firms in one of the technology parks in Malaysia, this paper provides an investigation on the relationship between social capital and technology transfer performance, within the technology park incubating company setting.It was found that social capital has significant relationships with the performance of technology transfer.